Designing walkable streets in congested touristic cities: the case of Cartagena de Indias, Colombia (2020)
This paper presents the case of Cartagena de Indias, a well-known international touristic destination in Colombia, which experiences serious problems of traffic congestion and accessibility to the city center. Promoting pedestrian mobility is one of the public administration’s main goals, by enhancing and re-designing different pedestrian paths. Designing pedestrian zones is a context-specific multifaceted problem that involves multiple stakeholders and multiple criteria. A participatory multicriteria approach based on the Analytic Network Process (ANP) has been used to understand the most important characteristics affecting pedestrian mobility in Cartagena de Indias, thus deriving a useful decision-support tool for planning and designing pedestrian paths. In this respect, in this paper a set of streets in the city center has been evaluated, by combining the results of ANP with spatial data using Geographic Information Systems (GIS), producing thematic maps and an index of pedestrian priority to derive a priority of intervention. Some streets have been redesigned with the aim to increase their walking attractiveness. Results put the basis for discussion with local administration and stakeholders to validate them and propose further applications of the methodology.